The epidemiology of infectious meningitis in Ghana: a systematic review and meta-analysis - Samuel A. Akwetey; Abdul-Halim Osman; Fleischer C. N. Kotey; Aaron Awere-Duodu; Alex Odoom; Bismark Opoku-Asare; Eric S. Donkor (BMC Public Health)
Abstract Background Meningitis is a significant health concern that is associated with high fatality rates, particularly in resource-limited settings such as Ghana, whose northern regions lie within the African Meningitis Belt. Despite the plethora of primary research data on meningitis in Ghana, a systematic review that provides comprehensive information to guide prevention, control, and management efforts is yet to be undertaken. This systematic review, therefore, aimed at bridging this gap by describing the epidemiology of meningitis in Ghana, including its prevalence, aetiology, and antimicrobial resistance. Method A comprehensive review of electronic databases, including PubMed and Scopus, was conducted between 2nd and 4th December, 2023, following the established PRISMA guidelines. The search encompassed articles published from 1975 to 2023. With no age limitations on study participants, data extraction was performed on peer-reviewed journal articles reporting primary findings. Studies that exclusively reported on meningitis in animal models, in vitro or in vivo were excluded. Studies with a sample size of less than ten were excluded from the analysis. A meta-analysis was carried out to determine the pooled estimate of meningitis prevalence in the country. Results There were 71,205 suspected meningitis cases analysed during the study period, with 3865 confirmed, and a pooled (overall) prevalence of 18.13%. Specifically, the cases that occurred during non-outbreak and outbreak periods had a pooled prevalence of 16.22% and 23.91%, respectively. The case fatality rates ranged from 20% to 47% between 1998 and 2015 and from 0.82% to 28.6% between 2016 and 2021. The three northern regions – Upper East (30.8%–54.35%), Northern (16.3%–46.4%), and Upper West (17.96%–38.8%) – had relatively high meningitis prevalence, while the Greater Accra and Ashanti Regions had prevalence ranging between 0.8% and 3.29%. Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae were the predominant isolates, accounting for 0.48%–77.7%, 2.5%–69.5%, and 0.90%–3.40% of the cases, respectively. All bacterial isolates from meningitis cases were susceptible to ceftriaxone. The most common Neisseria meningitidis serogroups were W135, A, Y, and X, while Serotype 1 dominated among the Streptococcus pneumoniae serotypes. Conclusion There is a disparity in the distribution of meningitis in Ghana, with the highest prevalence occurring in the northern parts of the country. There seems to have been a reduction in the case fatality rate over the years, probably due to interventions such as vaccinations. Ceftriaxone continues to be a suitable treatment option for meningitis. There should be continuous surveillance of meningitis aetiological agents — especially serotyping of the common pathogens — to help guide national vaccination policies and programmes.